Assessment of Growth and Carbon Stock of 6-Year-Old Dryobalanops lanceolata - Triatmojo, Muhammad Reza; Pamoengkas, Prijanto; Darwo (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
Dipterocarp species are the mainstay of forest products in the form of woodworking. Dryobalanops lanceolata is one of the dipterocarp species. The study aimed to analyze the effect of canopy cover on the growth and carbon storage of 6-year-old D. lanceolata. Data were collected by measuring diameter, height, canopy cover, soil samples, and carbon storage. The research method was carried out by regression between canopy cover and tree diameter and height growth, analyzing soil fertility and carbon content. The 6-year-old D. lanceolata has grown well with a canopy cover of less than 34% (canopy openness of more than 66%) and could grow on clay soil with acidic pH. D. lanceolata at the age of 6 years has been able to improve the nutrient content in the soil. Under 6-year-old D. lanceolata stands, it has provided significant changes to increase the availability of soil nutrients for C-organic, total N, and K-available content. Carbon storage in D. lanceolata has increased in 1 year by 41.91%. Keywords: biomass, canopy cover, carbon growth, Dryobalanops lanceolata